Impact of electrostatic doping level on the dissipative transport in graphene nanoribbons tunnel field-effect transistors. (November 2019) - Zhang, Weixiang; Ragab, Tarek; Zhang, Ji; Basaran, Cemal
Abstract: The impact of electrostatic doping level on the dissipative transport of Armchair GNR-TFET is studied using the Quantum Perturbation Theory (QPT) with the Extended Lowest Order Expansion (XLOE) implementation method. Results show that the doping level of the source and drain sides of the GNR-TFET has a significant impact on the phonon contribution to the carrier transport process. Unlike in other similar studies, where phonons are believed to have a constant detrimental influence on the ION /IOFF ratio and Subthreshold Swing (SS) of the TFET devices due to the phonon absorption-assisted tunneling, we show that by a proper engineering of the doping level in the source and drain, the phonon absorption assisted tunneling can be effectively inhibited. We also show that as temperature increase, the device switching property deteriorates in both the ballistic and dissipative transport regimes, and there exists a temperature-dependent critical doping level where the device has optimal switching behavior. Graphical abstract: Image 109